1992
DOI: 10.1021/bk-1992-0500.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Lipid Oxidative Processes and Their Inhibition

Abstract: A concise overview of the kinetics, energetics, and mechanisms of oxidative processes involving fatty acids in simple model systems relevant to autoxidation of foods is presented. Endogenous and exogenous factors that initiate oxidative processes in biochemical systems are reviewed and elements of and conditions for propaga tion of chain peroxidation processes are defined. Mechanistic aspects of chain-breaking antioxidants, including redox potentials, are presented. Biomarkers of fatty acid peroxidation are br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0
6

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 22 publications
2
28
0
6
Order By: Relevance
“…Many review articles have been written recently on its mechanisms, kinetics and products (1)(2)(3)(4), as well as on controlling it (5,6). The amount of unsaturated acyls and their degree of unsaturation are the most important factors affecting oxidation (1,3,4,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many review articles have been written recently on its mechanisms, kinetics and products (1)(2)(3)(4), as well as on controlling it (5,6). The amount of unsaturated acyls and their degree of unsaturation are the most important factors affecting oxidation (1,3,4,7).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of unsaturated acyls and their degree of unsaturation are the most important factors affecting oxidation (1,3,4,7). Other factors controlling oxidizability are position of unsaturated acyls in the triacylglycerols (TAGs) (7)(8), and the presence and interference of anti-and pro-oxidants (1,2). Comparison of oxidation studies is very difficult because the experimental conditions affect which reaction routes take place, and the analytical methods determine which reactions and products are looked at.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of autoxidation have usually been considered for the individual steps (Labuza, 1971;Brimberg, 1993;Simic et a/., 1992). …”
mentioning
confidence: 99%
“…[1][2][3] ÄOzilgen and ÄOzilgen 4) have reported that a kinetic expression of the autocatalytic type in terms of the fraction of the unoxidized substrate could describe the entire oxidation process of some lipids. We have also reported that the expression was applicable to the entire oxidation process of n-6 fatty acids, their methyl or ethyl esters 5) and their acylglycerols, 6) and to theˆrst half of the oxidation process of n-3 fatty acids, their esters 5) and their acylglycerols.…”
mentioning
confidence: 99%